Theoretical Analysis of the Cooperative Learning Model in Islamic Religious Education Learning: A Literature Review of Its Effectiveness and Implementation - Syamsul Maarif (Jurnal Iman dan Spiritualitas, 2026)
This study aims to formulate a conceptual framework for the “Integrated Cooperative Learning Model in Islamic Religious Education (PAI)” that combines the advantages of Jigsaw, STAD, and Group Investigation with Islamic values ​​to improve student learning outcomes. The method used is library research with a descriptive-analytical approach, including identification and selection of international and national literature Sinta 1–3 (2015–2025), content analysis, and meta-synthesis to synthesize model components, pedagogical principles, and implementation mechanisms. The results of the study indicate four core components, namely heterogeneous group organization, cooperative tasks based on the values ​​of ukhūwah, ta’āwun, ikhlas, and amanah, individual and team responsibility, and joint evaluation, which are proven to predict an average increase in cognitive ≥ 15%, affective ≥ 12%, and psychomotor ≥ 10%. This model also maps three predictors of successful implementation in madrasas: facilitator quality, balance between structure and freedom of discussion, and curriculum support. In conclusion, this conceptual framework not only addresses theoretical needs but also provides practical guidance for Islamic Religious Education educators and proposes a foundation for future field research and curriculum policy development.